2020
DOI: 10.1186/s12888-020-02803-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors for involuntary psychiatric hospitalization: using environmental socioeconomic data and methods of machine learning to improve prediction

Abstract: Background The purpose of this study was to identify factors associated with a high risk of involuntary psychiatric in-patient hospitalization both on the individual level and on the level of mental health services and the socioeconomic environment that patients live in. Methods The present study expands on a previous analysis of the health records of 5764 cases admitted as in-patients in the four psychiatric hospitals of the Metropolitan City of Cologne, Germany, in the year 2011 (1773 cases treated under t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 59 publications
(105 reference statements)
0
11
2
Order By: Relevance
“…Self-injury/suicidal behaviors were not significantly different between two groups. These findings are different from previous reports ( 33 , 34 ). One research showed suicide attempts and affective disorders were strongly associated with involuntary psychiatric hospitalization among children and adolescents ( 35 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Self-injury/suicidal behaviors were not significantly different between two groups. These findings are different from previous reports ( 33 , 34 ). One research showed suicide attempts and affective disorders were strongly associated with involuntary psychiatric hospitalization among children and adolescents ( 35 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Involuntary admission has been shown to be associated with reduced adherence to community treatment. 35 , 36 Our intervention, assuming as it did a high degree of flexibility in the activities that took place, might not have been sufficiently structured either to maintain engagement or to meet the high level of need of our high-risk group of patients. A more structured intervention, as successfully delivered in a trial of peer supported self-management to reduce acute service use after discharge from crisis resolution and home treatment team care, 37 might have been of increased benefit to this population.…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have been made to address risk factors of IA. Some frequently reported predictors of IA include male gender [15,16], immigrant status [5,16,17], lower socioeconomic status and lack of social support [2,3,15,18], admission outside of regular service hours [2,5,16,19], and previous IA [20]. Comprising between 30% and 50% of involuntarily admitted patients in Europe, one of the most commonly reported predictors of IA is schizophrenia or related psychotic conditions [2,11,15,16,20,21].…”
Section: Introductionmentioning
confidence: 99%